The impact of government ownership on bank risk - Iannotta, Giuliano; Nocera, Giacomo; Sironi, Andrea (Journal of Financial Intermediation, 2013)
We use cross-country data on a sample of large European banks to evaluate the impact of government ownership on bank risk. We distinguish between default risk (likelihood of creditors’ losses) and operating risk (likelihood of negative equity). Our analysis is based on the joint use of issuer ratings, a synthetic measure of a bank’s probability of default, and individual ratings, which omit the influence of any external support and focus on a bank’s operating risk. We report two main results. First, government-owned banks (GOBs) have lower default risk but higher operating risk than private banks, indicating the presence of governmental protection that induces higher risk taking. Second, GOBs’ operating risk and governmental protection tend to increase in election years. These results are consistent with the idea that GOBs pursue political goals and have important policy implications for recently nationalized European banks.